1994
DOI: 10.1016/s0009-2509(05)80060-0
|View full text |Cite
|
Sign up to set email alerts
|

Transient drift spectroscopy for the determination of the surface reaction kinetics of CO2 methanation

Abstract: Abstract--Transient experiments were applied to the study of the adsorbed CO intermediate, (CO),,, formed during the CO2 methanation reaction on a 2% Ru/TiO2 catalyst at 383 K.Step-up experiments showed that the (CO),, formation steps are inhibited by H20 and enhanced by H 2.Step-down experiments showed that the (CO),, hydrogenation is not influenced by the partial pressure of water. Based on the fact that water inhibits the overall CO 2 methanation, it is deduced that the rate limiting process in the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
6
25
0
Order By: Relevance
“…The observed electrophobic behavior (@r/@U WR > 0) for the methanation reaction and the observed electrophilic behavior (@r/@U WR < 0) for the RWGS reaction (Figures 2 and 3) is consistent with the rules of chemical and electrochemical promotion. [37,38] Indeed, as already reported in our previous study [45] and other recent studies, [11,12,47,48] and as shown in Figure 4, under the gas conditions of Figure 2, the rate of the methanation reaction has a positive order in reactant D (H 2 , reaction order ca. 1) and negative order in reactant A (CO 2 , reaction order near À1); thus, the promotional rules predict electrophobic behavior (@r/@U WR > 0), as experimentally observed (Figures 2 and 3).…”
Section: Resultssupporting
confidence: 81%
“…The observed electrophobic behavior (@r/@U WR > 0) for the methanation reaction and the observed electrophilic behavior (@r/@U WR < 0) for the RWGS reaction (Figures 2 and 3) is consistent with the rules of chemical and electrochemical promotion. [37,38] Indeed, as already reported in our previous study [45] and other recent studies, [11,12,47,48] and as shown in Figure 4, under the gas conditions of Figure 2, the rate of the methanation reaction has a positive order in reactant D (H 2 , reaction order ca. 1) and negative order in reactant A (CO 2 , reaction order near À1); thus, the promotional rules predict electrophobic behavior (@r/@U WR > 0), as experimentally observed (Figures 2 and 3).…”
Section: Resultssupporting
confidence: 81%
“…6c) and was ascribed to a surface formate species (HCO 2 − ) 47,48 ; this assignment is supported by an additional peak observed at 2814 cm −1 (Fig. 6d) 11,49 . It is noteworthy that the peak intensity of this formate species is much higher than that of the carbonate species.…”
Section: Resultsmentioning
confidence: 66%
“…A schematic representation is given by Marwood et al [7]. Approximately 0.06-0.08 g of the sample was placed in the sample holder of the DRIFTS cell.…”
Section: Methodsmentioning
confidence: 99%
“…These ordered structures are stabilized by hydrogen and destroyed by water during the transient hydrogenation experiments. It has been shown previously [7] that within a certain hydrogen and water concentration range (5-20% H 2 and PR2o = 2.6-12.3 mbar), the hydrogenation of (CO) a exhibits a first-order dependence on the carbon monoxide surface coverage (Eq. (5)).…”
Section: Adsorbed Carbon Monoxidementioning
confidence: 99%